The SEI's Outreach - McGill (Desautels Faculty of Management)
The SEI's outreach-related goal is to provide catalyzing experiential learning opportunities outside the classroom for our students by engaging with individuals and organizations active in the social economy. Mary Gordon, Founder, Roots of Empathy The SEI regularly organizes outreach events for students and the general public. Consult our News and Events Channels for more information on past and future SEI events. The SEI Impact Internship Program was launched in summer 2013. The program offers high-quality internships in non-profit organizations that, while promoting academic, network and personal development, contribute to positive social change. The SEI is also proud to support the McGill Dobson Cup with the Social Entrepreneurship track. For more information, see Dobson Cup Boot Camp Social Entrepreneurship Track. Desautels Faculty of Management students are engaged in a multitude of outreach initiatives that fall within the purview of the social economy, including: Student groups: MBA Net Impact, Management Sustainability Network, CASCO (Commerce and Administration Student Charity Organization), McGill Sustainable Healthcare Initiative, Right to Play McGill, etc. Conferences: Desautels Business Conference on Sustainability, Leadership and Social Change Fair, etc. Consulting: McGill Not-for-Profit Consulting.